Labyrinthectomy and Vestibular Neurectomy for Intractable Vertiginous Symptoms - Vega Alarcón, Alfredo; Vales Hidalgo, Lourdes Olivia; Jácome Arévalo, Rodrigo; Palma Diaz, Marite (International Archives of Otorhinolaryngology, 2017)
Introduction Labyrinthectomy and vestibular neurectomy are considered the surgical procedures with the highest possibility of controlling medically untreatable incapacitating vertigo. Ironically, after 100 years of the introduction of both transmastoid labyrinthectomy and vestibular neurectomy, the choice of which procedure to use rests primarily on the evaluation of the hearing and of the surgical morbidity.Objective To review surgical labyrinthectomy and vestibular neurectomy for the treatment of incapacitating vestibular disorders.Data Sources PubMed, MD consult and Ovid-SP databases.Data Synthesis In this review we describe and compare surgical labyrinthectomy and vestibular neurectomy. A contrast between surgical and chemical labyrinthectomy is also examined. Proper candidate selection, success in vertigo control and complication rates are discussed on the basis of a literature review.Conclusions Vestibular nerve section and labyrinthectomy achieve high and comparable rates of vertigo control. Even though vestibular neurectomy is considered a hearing sparing surgery, since it is an intradural procedure, it carries a greater risk of complications than transmastoid labyrinthectomy. Furthermore, since many patients whose hearing is preserved with vestibular nerve section may ultimately lose that hearing, the long-term value of hearing preservation is not well established. Although the combination of both procedures, in the form of a translabyrinthine vestibular nerve section, is the most certain way to ablate vestibular function for patients with no useful hearing and disabling vertigo, some advocate for transmastoid labyrinthectomy alone, considering that avoiding opening the subarachnoid space minimizes the possible intracranial complications. Chemical labyrinthectomy may be considered a safer alternative, but the risks of hearing loss when hearing preservation is desired are also high.
Keywords: vestibular diseases/surgery; labyrinth diseases/surgery; Ménière's disease/surgery; neuritis/surgery; vertigo/surgery; vestibular nerve/surgery; vestibulocochlear nerve diseases/surgery